Krvaveč Mecklov divertikel - laparoskopski pristop - Černi, Igor (Endoskopska revija, 2012)
Meckel's diverticulum is the most common anomaly of the small intestine, with an incidence of approximately 2%. It is usually located on the antimesenteric side of the ileum and is 0.5 to 56 cm long. It is distinguished from other diverticula in being composed of all the layers of the intestinal walls and having its own circulation. Heterotopic tissue may be present in Meckelćs diverticulum, most commonly including gastric mucosa (62%), and less frequently pancreatic (6%) or duodenal tissue. It is three to four times more common in men than in women. The most frequent complications include bleeding,intestinal obstruction and diverticulitis. We present a case of a 20-year-old patient who had an emergency laproscopic resection of the segment of small intestine containing a Meckelćs diverticulum with intraabdominal anastomosis using a stapler.
Keywords: Meckelov divertikel; Meckel'S Diverticulum; Complications; Gastrointestinalna krvavitev; Gastrointestinal Hemorrhage; Zdravljenje, izid; Odrasli; Surgery, Laparoscopic; tanko črevo; Treatment Outcome; krvavitev; Adult; laparoskopska kirurgija